2019
DOI: 10.1093/mnras/stz2570
|View full text |Cite
|
Sign up to set email alerts
|

X-ray spectral analysis of the neutron star in SNR 1E 0102.2−7219

Abstract: We re-analysed numerous archival Chandra X-ray observations of the bright supernova remnant (SNR) 1E 0102.2-7219 in the Small Magellanic Cloud, to validate the detection of a neutron star (NS) in the SNR by Vogt et al. (2018). Careful attention to the background is necessary in this spectral analysis. We find that a blackbody + power-law model is a decent fit, suggestive of a relatively strong B field and synchrotron radiation, as in a normal young pulsar, though the thermal luminosity would be unusually high … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 92 publications
(135 reference statements)
0
17
0
Order By: Relevance
“…Janka (2017) found that, for 2D and 3D simulations, a high level of explosion asymmetry (common in high mass progenitor systems) can cause higher kick velocities. Hebbar et al (2020) and Xi et al (2020) each conducted a careful analysis of Chandra observations of the candidate CCO that included time-dependent responses for each of the archival observations, modeling of the background instead of subtracting it, and fitting the unbinned spectra to preserve the maximal spectral information. Hebbar et al (2020) found that a single blackbody model does not provide an acceptable fit to the data, but a blackbody+power-law or a neutron star carbon atmosphere model do provide acceptable fits.…”
Section: Proposed Cco Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Janka (2017) found that, for 2D and 3D simulations, a high level of explosion asymmetry (common in high mass progenitor systems) can cause higher kick velocities. Hebbar et al (2020) and Xi et al (2020) each conducted a careful analysis of Chandra observations of the candidate CCO that included time-dependent responses for each of the archival observations, modeling of the background instead of subtracting it, and fitting the unbinned spectra to preserve the maximal spectral information. Hebbar et al (2020) found that a single blackbody model does not provide an acceptable fit to the data, but a blackbody+power-law or a neutron star carbon atmosphere model do provide acceptable fits.…”
Section: Proposed Cco Resultsmentioning
confidence: 99%
“…Hebbar et al (2020) and Xi et al (2020) each conducted a careful analysis of Chandra observations of the candidate CCO that included time-dependent responses for each of the archival observations, modeling of the background instead of subtracting it, and fitting the unbinned spectra to preserve the maximal spectral information. Hebbar et al (2020) found that a single blackbody model does not provide an acceptable fit to the data, but a blackbody+power-law or a neutron star carbon atmosphere model do provide acceptable fits. However, the blackbody+power-law model fit has a neutral hydrogen column density that is ∼ 10× higher than the accepted value to E0102 and the neutron star carbon atmosphere model has a value that is ∼ 18× higher.…”
Section: Proposed Cco Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, its X-ray spectrum is thermal, ★ E-mail: pshternin@gmail.com shows little or no pulsations and can be described by the emission from the whole NS surface if a carbon atmosphere is assumed (Ho & Heinke 2009; see also Chang, Bildsten & Arras 2010;Wijngaarden et al 2019). It was the first NS for which the carbon atmosphere model had been successfully applied; several more such sources are known now (see, e.g., Klochkov et al 2013Klochkov et al , 2016Doroshenko et al 2018;Hebbar et al 2020;Ho et al 2021). Second, the star probably shows real-time cooling, much faster than expected from the standard NS cooling models.…”
Section: Introductionmentioning
confidence: 99%
“…Near the geometric center of Cas A exists an X-ray point source that is likely the NS produced by the SN of Cas A (Tananbaum 1999;Chakrabarty et al 2001), and E0102 may also have a NS within its boundary albeit at an off-center position (Vogt et al 2018). While the NS in E0102 is confirmed by Hebbar et al (2020), it is also challenged by Long et al (2020), who suggest that the X-ray source is an ejecta knot rather than a NS. Within Cas A, fast hydrogen-rich knots were detected to have velocities ∼ 6000 km s −1 , implying condensations from the progenitor's outer layers (Fesen et al 1988;Fesen & Becker 1991), and in E0102 a small amount of fast-moving hydrogen-rich ejecta material is observed to have velocities up to 1785 km s −1 (Seitenzahl et al 2018).…”
mentioning
confidence: 99%